Aspekter på flyttkostnader, fastighetsbildning och fastighetstorlekar - Ekholm, Anders (2007)
This master thesis has three purposes. The first purpose is to give a theoretical background of how to divide up forest estates and to study how the legal system for these matters works. A literature study has been carried out to give the background and a theoretical model has been made for analysing the law cases. The first purpose also partly touched the decision process in dividing up forest estates from point of view of the law of land parcelling (FBL), point of view.